The growth of ice particles in a mixed phase environment based on laboratory observations - Castellano, Nesvit Edit (2014)
Fil: Castellano, Nesvit Edit. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.